Use of 18F-fluorodeoxyglucose positron emission tomography-computed tomography in patients affected by polymyalgia rheumatica and persistent increase of acute phase reactants - Colaci, Michele; Dichiara, Jessika; Aprile, Maria Letizia; Ippolito, Massimo; Schinocca, Claudia; Guggino, Giuliana; Malatino, Lorenzo (Frontiers in Medicine, 2022)
Polymyalgia rheumatica (PMR) is an inflammatory disease affecting older adults that can be associated with giant cell arteritis (GCA). Generally, PMR is highly responsive to steroids, reaching complete remission in the majority of cases. However, the possibility of occult diseases, including extra-cranial GCA, should be excluded. [18F]FDG-PET is able to detect the presence of peri-/articular or vascular inflammation, which may be both present in PMR. We retrospectively evaluated all consecutive patients who received the diagnosis of PMR in our rheumatology clinic in the period between April 2020 and May 2022. Then, we selected the patients who underwent [18F]-FDG-positron emission tomography (PET) because of the persistent increase of acute phase reactants (APR) besides the steroid therapy. Eighty patients (mean age 71.7±7.6 years; M/F 2/14) were diagnosed with PMR and none showed signs of cranial GCA at the diagnosis. Seventeen subjects presented persistent increase of erythrocyte sedimentation rate (mean ESR 44.2±11.5 mm/h) and/or C-reactive protein (mean CRP 25.1±18.2 mg/L), thus they underwent total body [18F]-FDG-PET. Large vessel FDG uptake indicating an occult GCA was found in 5/17 (29.4%) cases; 12/17 (70.6%) patients showed persistence of peri-/articular inflammation, suggesting a scarce control of PMR or the presence of chronic arthritis. Finally, in 2 cases, an acute thyroiditis and a hip prosthesis occult infection were found. [18F]-FDG-PET in PMR patients with persistent increase of APR is a useful diagnostic technique in order to detect occult GCA, persistence of active PMR or other misdiagnosed inflammatory diseases.